Methicillin Resistance and Slime Positivity of Coagulase Negative and Positive Staphylococci Isolated From Nares of Healthcare Workers - Çelik, İlhami; Cihangiroğlu, Mustafa; Sevim, Erol; Çabalak, Mehmet; Akbulut, Ayhan (Fırat University, 2005)
Objectives: It was aimed to detect the prevalence of nasal carriage of methicillin-resistant Staphylococcus aureus and Coagulase negative staphylococci (CoNS) of the healthcare personnel in our hospital and if any relation with slime production and methicillin resistance in these strains. Materials and Methods: Specimens for culture were collected from the anterior nares from healthcare personnel with sterile cotton swabs. The nasal swabs were cultured on 5% sheep blood agar plates and incubated at 37ºC for 24-hour. Coagulase tests were performed for the strains identified with colony morphology and Gram staining. The susceptibilities of the isolates to oxacillin were determined by the disk diffusion method according to National Committee for Clinical Laboratory Standards. Slime production was investigated by Congo Red Agar plate method. Results: When thirty-seven (31.4%) of the isolated strains were S. aureus, and 35.1% of these were methicillin-resistant, methicillin resistance was 59.3% for CoNS (p=0.015). Slime positivity was 73% at S. aureus strains, and 65.4% for CoNS (p=0.4). It was detected a risk factor that studying at surgical departments (%23.1 vs. %76.9, r= 0.48, %95 CI: 0.196-0.768, p=0.002). Conclusion: The potential of slime production was observed higher at MR staphylococci. No methicillin resitancy was observed at slime produced species, but it was observed a high prevalence rate of MRSA carriage. Thus, it proposes that it needs to continuing education for hospital infection control and applicable and permanent solution for eradication of MRSA. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Bu çalışmada, sağlık çalışanlarının burunlarında metisilin dirençli Staphylococcus aureus (MRSA) ve koagülaz negatif stafilokok taşıyıcılık oranı ve bu suşlarda metisilin direnci ile slime oluşumu arasında ilişki olup olmadığının irdelenmesi amaçlandı. Gereç ve Yöntem: Steril eküvyonlu çubuklarla 118 hastane çalışanının her iki burun mukozalarından alınan sürüntü kültürleri %5 koyun kanlı agara ekilerek 35ºC'de 24 saat inkübe edildi. Koloni morfolojisi ve Gram boyama ile stafilokok olarak tanımlanan suşlar için koagülaz testi yapıldı. Metisilin direnci (oksasilin direnci) NCCLS önerilerine göre disk difüzyon yöntemi ile belirlendi. Slime oluşumu Kongo Red Agar plak yöntemiyle araştırıldı. Bulgular: İzole edilen suşların 37'si (%31,4) S. aureus ve bunların %35.1'i metisiline dirençli iken KNS suşlarında metisilin direnci %59.3 idi (p=0.015). S. aureus suşlarında slime pozitiflik oranı %73, KNS suşlarında %65.4 idi (p=0.4). Cerrahi kliniklerde çalışmanın MRSA taşıyıcılığı için bir risk faktörü olduğu saptandı (%23.1'e karşı %76.9, r= 0.48, %95 güvenilirlik aralığı: 0.196–0.768, p=0.002). Sonuç: Metisiline dirençli stafilokoklarda slime oluşturma potansiyeli oldukça yüksek oranda saptandı. Slime oluşturan suşlarda metisilin direncinde artış gözlenmedi ancak MRSA taşıyıcılık oranının oldukça yüksek düzeyde olduğu göz önüne alınırsa hastane infeksiyonlarının kontrolü için yapılan eğitimlerin sürekliliğine ve MRSA eradikasyonu için uygulanabilir ve kalıcı çözümlere ihtiyaç vardır. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Sağlık Çalışanlarının Burunlarından İzole Edilen Koagülaz Pozitif ve Negatif Stafilokoklarda Metisilin Direnci ve Slime Pozitifliği